EXTRACTION TOTAL PHENOLIC CONTENT OF KETAPANG LEAVES (Terminalia catappa) USING ULTRASONIC - Sari, Denni Kartika; Lestari, Retno Sulistyo Dhamar; M, Muhammad Ridho K.; Lusi, Utami Triana (World Chemical Engineering Journal, 2018)
Ketapang leaves (Terminalia catappa) is a plant which has many pharmacological activities one of them is antioxidat activity.  Phenolic compound is one that represented the antioxidant activity. The concentration of phenolic compounds was influenced by the method and condition of extraction. This study was conducted to determine the effect of ultrasonic extraction method, extraction time and the ratio of ethanol : water to total phenolic content in Ketapang leaves (Terminalia catappa). Extraction is completed by ultrasonic extraction method using 96% ethanol-water as solvent with solvent ratio variation (50:50, 60:40, 70:30) in time (5 minutes, 10 minutes, 20 minutes and 40 minutes). Measurment data from total phenolic content of the extracts Ketapang leaves (Terminalia catappa) shows that the extraction with 20 minutes with 96% ethanol-water 50:50 generate the highest total phenolic content, equal to 4862,352941mg GAE / g.